Improved Executive Function in Adults Diagnosed With Attention-Deficit/ Hyperactivity Disorder as Measured by the Brown Attention-Deficit Disorder Scale Following Treatment With SHP465 Mixed Amphetamine Salts Extended-Release: Post Hoc Analyses From 2 Randomized, Placebo-Controlled Studies. Issue 2 (January 2022) - Brown, Thomas E.; Chen, Jie; Robertson, Brigitte
Objective: Assess executive function (EF) improvement with SHP465 mixed amphetamine salts (MAS) extended-release in adults with attention-deficit/hyperactivity disorder (ADHD) using responder analyses of the Brown Attention-Deficit Disorder Scale (BADDS). Methods: Post hoc analyses examined data from placebo-controlled SHP465 MAS dose-optimization (12.5–75 mg) and fixed-dose (25–75 mg) studies. Treatment response was assessed using two definitions (BADDS total score at endpoint <50 [no EF impairment] vs. ≥50 [impaired]; BADDS total score at endpoint relative to the in-treatment 90% CI range for baseline total score [below the range = improved]). Results: Response rates (SHP465 MAS vs. placebo) favored SHP465 MAS (all nominal p < .0001) in the dose-optimization (BADDS <50: 41.9% vs. 19.2%; below 90% CI range: 57.4% vs. 29.6%) and fixed-dose (BADDS <50: 51.9% vs. 16.7%; below 90% CI range: 70.6% vs. 32.3%) studies. Conclusion: Improvement in EF measured by BADDS response rates was approximately 2-fold greater with SHP465 MAS than placebo.